PENGARUH PENGGUNAAN MEDIA VIDEO ANIMASI TERHADAP HASIL BELAJAR IPAS PADA MATERI KEGIATAN EKONOMI DI INDONESIA SISWA KELAS IV SDN 42 PEKANBARU - Meysi Aprima Putri; Laili Rahmi (STKIP Subang, 2024)
This research aims to determine the effect of using animated video media on science learning outcomes on economic activity material in Indonesia. This research was carried out in class IV at SDN 42 Pekanbaru. This research is a type of quasi-experimental research, with a non-equally control group design. The population in this study were all class IV students at SDN 42 Pekanbaru. The sample for this research was 33 class IVA students in the control group, and 32 class IVB students in the experimental group. Determination of the sample using purposive random sampling technique. The results of the research show that the use of animated video learning media in science and science learning has a significant influence on the learning outcomes of fourth grade elementary school students. These findings support innovative approaches to education that emphasize the use of technology to improve the quality of learning. The use of animated video learning media not only meets the needs of contemporary education that is more visual and interactive, but also makes a real contribution to improving student learning outcomes.